The Mawardi Muhammad’s Hadith Thought in Hidayah Al-Bahits fi Mushthalah Al-Hadits - Muhammad Fauzhan 'Azima (Institut Agama Islam Sumatera Barat, 2023)
The hadith thought of Mawardi Muhammad in his book Hidayah al-Bahits fi Mushthalah al-Hadits is interesting to study. This is because the book written in arabic received a positive response from students of hadith studies and ulumul hadith in the Nusantara. Even though Mawardi Muhammad is a non-Arab scholar and has never studied in the Middle East which is actually the center of hadith and ulumul hadith studies. This study aims to find out the hadith thought of Mawardi Muhammad in his masterpiece, the book Hidayah al-Bahits fi Mushthalah al-Hadits. The research method used in this paper is a qualitative research method with the type of library research research. The results of this study show that among the thoughts of Mawardi Muhammad's hadith in the book Hidayah al-Bahits fi Mushthalah al-Hadits are his thoughts regarding the classification of hadith, the minimum limit on the number of narrators of hadith mutawatir, and the definition of hadith dha'if and the law of practicing it. Regarding the classification of hadith, Mawardi Muhammad put the types of hadith masyhur, 'aziz, shahih, hasan, and dha'if in one classification. Regarding the minimum limit on the number of hadith mutawatir narrators, Mawardi Muhammad argued that there was no clear limit in this regard while criticizing the opinion that mentioned certain numbers for the minimum limit on the number of mutawatir hadith narrators. Then in the case of hadith dha'if, Mawardi Muhammad is a scholar who has manhaj mutawasith, which is open to the practice of hadith dha'if with certain conditions.